2008
DOI: 10.1142/s0218625x08011664
|View full text |Cite
|
Sign up to set email alerts
|

A NEW METHOD TO PREPARE THE NOVEL ANATASE TiO2

Abstract: In this paper, a kind of novel anatase TiO 2 nanoparticle with single-electron-trapped oxygen vacancies was prepared by hydrothermal treated nanotube titanic acid. The morphology, structure, and properties of the products were characterized by transmission electron microscope, X-ray diffraction, electron spin resonance, and photoluminescence. Photocatalytic decolorization of the Methylene Blue solution was carried out in the visible light region and showed a high photocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
0
1
Order By: Relevance
“…4(b) shows the effect of hydrothermal reaction temperature on the absorption of the BiOCl composited samples. It can be seen that the visible light absorption intensity of these samples was similar despite the increase in reaction temperature, which is in agreement with reports from the literature [40].…”
Section: Xps Studysupporting
confidence: 92%
See 1 more Smart Citation
“…4(b) shows the effect of hydrothermal reaction temperature on the absorption of the BiOCl composited samples. It can be seen that the visible light absorption intensity of these samples was similar despite the increase in reaction temperature, which is in agreement with reports from the literature [40].…”
Section: Xps Studysupporting
confidence: 92%
“…Our previous studies have indicated that hydrothermal treatment of NTA generates large amounts of single-electron-trapped oxygen vacancies (SETOVs). These SETOVs form an intra-band level below the conduction band, which contributes to visible light absorption [40][41][42]. So, we can ascribe the visible-light absorption of the BiOCl composited TiO2 catalysts in the present work to the formation of SETOVs during the process of NTA hydrothermal treatment.…”
Section: Xps Studymentioning
confidence: 69%
“…Samples N-NTA-130 and N-NTA-160 still retain the orthorhombic form (inset in Figure 1) and nanotubular morphology of precursor NTA ( Figure 2). This differs from our previous finding in that the tubular shape of orthorhombic NTA is destroyed in association with conversion into anatase TiO 2 when NTA is heated in distilled water at 130 • C or 160 • C [15]. However, sample N-NTA-210 shows strong diffraction peaks of anatase TiO 2 as well as additional diffraction peaks of rutile phase (27.4, 36.1, 39.2, 41.2, 44.1, and 56.6 • ), which indicates that hydrothermal treatment of orthorhombic NTA in ammonia solution at an elevated temperature of 210 • C also facilitates its transformation to TiO 2 .…”
Section: Resultscontrasting
confidence: 99%